FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA DAN MALAYSIA (Meta-Analisis Penelitian di Indonesia dan Malaysia Tahun 2010-2016) - Ribut Pipit Agustina; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This study focuses upon the influence between banking internal factors and economic macro on the Islamic banking profitability in Indonesia and Malaysia of the last seven years researches to determine profitability predictor variables of them. Meta-analysis techniques developed by Hunter et al. (1982) were performed to some existing studies. Profit and loss sharing financing and interest rates of BI have a significant correlation to the Indonesia Islamic banking profitability, while the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and inflation have nosignificant correlation. Meta-analysis result of Islamic banking in Malaysia shows that total asset, loan to total asset, equity to total asset, expenses management, loan loss reserve to gross loan, and money supply (M2) have a significant correlation to the profitability of Malaysia Islamic Banking, whilst liquidity (liq) and GDP have no significant correlation.   REFERENCESAbduh, Muhamad & Yameen Idrees. 2013. Determinants of Islamic Banking Profitability in Malaysia. Australian Journal of Basic and Applied Sciences, VII (2): 204-210.Abdurrahman dkk. 2014. Analisis Pengaruh Jumlah Kredit Mikro yang Diberikan dan Non Performing Loan Terhadap Profitabilitas pada PT.Bank Syariah Mandiri KCP Buleleng Periode Tahun 2012-2013. e-Journal S1 Ak Universitas Pendidikan Ganesha, II (1).Alhamditia, Era Rizkita & Mohamad Heykal. 2013. Analisis Estimasi dan Faktor-faktor yang Memengaruhi Tingkat Profitabilitas Bank Umum Syariah di Indonesia. Binus Business Review, IV (1): 186-196.Amelia, Erika. 2015. Financial Rasio and Its Influence to Profitability in Islamic Banks. Al Iqtishad, VII (2): 229-240.Chowdhury, Mohammad Ashraful Ferdous. 2015. Which is more important in terms of Profitability of Islamic Banks: Bank Specific factors or Macroeconomic factors? An Empirical Study on Malaysian Islamic Banks.Bangladesh. Departement of Business Administration. Shahjajalal University of Science & Technology.Chua, Siti Zulaiha Muhd Zamri. 2012. Determinants of Islamic Banks Profitability in Malaysia. Berjaya Ad-ira Institution Centre.Dahliawati, Anne & Muhammad Muchlis Febrianto. 2012. Analisis Pengaruh Capital Adequacy Ratio (CAR) dan Aktiva Tetap Terhadap Modal (ATTM) Terhadap Profitabilitas (ROA) pada PT.Bank “X” Syariah Periode 2009-2011. UG Jurnal, VI (11).Dendawijaya, Lukman. 2003. Manajemen Perbankan. Edisi: 2. Jakarta: Ghalia Indonesia.Fanani, Zaenal. 2014. Karakteristik Perusahaan dan Corporate Governance terhadap Manajemen Laba: Studi Analisis Meta. Jurnal Keuangan dan Perbankan, XVIII(2): 181-200.Hakiim, Ningsukma & Haqiqi Rafsanjani. 2016. Pengaruh Internal Capital Adequacy Ratio (CAR), Financing To Deposit Ratio (FDR), dan Biaya Operasional Per Pendapatan Operasional (BOPO) dalam Peningkatan Profitabilitas Industri Bank Syariah di Indonesia. Jurnal Aplikasi Manajemen, XIV(1): 161-168.Hidayati, Amalia Nuril. 2014. Pengaruh Inflasi, BI Rate dan Kurs Terhadap Profitabilitas Bank Syariah di Indonesia. An-Nisbah, I (1): 72-97.Hunter, J.E., and F.L.Schmidt. 1990. Methods of Meta Analysis: Correcting Error and Bias in Research Findings. Beverly Hills, CA:Sage.Husain, Azira dkk. 2015.  The Internal Determinants of Islamic Banks Profitability in Malaysia. Journal of Basic and Applied Scientific Research. V (7): 17-21.Idris, Asma Rashidah dkk. 2011. Determinant of Islamic Banking Institutions Profitability in Malaysia. World Applied Sciences Journal 12.Kasmir. 2014. Analisis Laporan Keuangan. Jakarta: Rajawali Persada.Kok, Yoke Teng dkk. 2012. The Determinants of Islamic Banks Profitability in Malaysia. Malaysia. Faculty of Business and Finance. Universiti Tunku Abdul Rahman.Lyons, Larry C. 2000. Meta Analysis: Methods of Accumulating Results Accross Research Domains. Email Solomon@mnsinc.comMaharanie, Mega Ayu & Sri Herianingrum. 2014. Pengaruh Kecukupan Modal, Fungsi Intermediasi, Pembiayaan Bermasalah, dan Biaya Operasional Terhadap Profitabilitas Industri Bank Syariah Periode Januari 2010-Desember 2012. JESTT, I ( 2).Ma’isyah, Rifqul & Imron Mawardi. 2015. Pengaruh Kecukupan Modal, Fungsi Intermediasi, Efisiensi Operasional, dan Pembiayaan Bermasalah Terhadap Profitabilitas: Studi pada Bank Syariah Periode Januari 2010-Juli 2014. JESTT, II (3): 249-265.Pramuka, Bambang Agus. 2010. Faktor-Faktor yang Berpengaruh Terhadap Tingkat Profitabilitas Bank Umum Syariah. Jurnal Akuntansi, Manajemen Bisnis dan Sektor Publik (JAMBSP), VII (1): 63-79.Riyadi, Slamet & Agung Yulianto. 2014. Pengaruh Pembiayaan Bagi Hasil, Pembiayaan Jual Beli, Financing to Deposit Rasio dan Non Performing Financing Terhadap Profitabilitas Bank Umum Syariah di Indonesia. AAJ, III(4): 466-474.Sodiq, Amirus. 2015. Pengaruh Variabel Makro Ekonomi Terhadap Profitabilitas Bank Syariah di Indonesia Periode 2009-2014. BISNIS, III (2): 343-363.Soemitra, Andri. 2010. Bank dan Lembaga Keuangan Syariah. Edisi 1. Jakarta: Kencana Prenada Media Group.Sukirno. Sadono. 2010. Teori Pengantar Ekonomi Makro. Jakarta: PT.Raja Grafindo Persada.Suryani. 2011. Analisis Pengaruh Financing to Deposit Ratio (FDR) Terhadap Profitabilitas Perbankan Syariah Di Indonesia. Walisongo, XIX(1): 47-74.Swandayani, Desi Marilin & Rohmawati Kusumaningtias. 2012. Pengaruh Inflasi, Suku Bunga, Nilai Tukar Valas dan Jumlah Uang Beredar Terhadap Profitabilitas pada Perbankan Syariah di Indonesia Periode 2005-2009. AKRUAL, III (2): 147-166.Ubaidillah. 2016. Analisis Faktor-Faktor yang Mempengaruhi ProfitabilitasBank Syariah di Indonesia. el-JIZYA: Jurnal Ekonomi Islam, IV(1): 151-188.Wasiuzzaman, Shaista & Hanimas Ayu Bt Ahmad Tarmizi. 2010. Profitability of Islamic Banks in Malaysia: An Empirical Analysis. Journal of Islamic Economics, Banking and Finance, VI (4).Wibowo, Edhi Satriyo & Muhammad Syaichu. 2013. Analisis Pengaruh Suku Bunga, Inflasi, CAR, BOPO, NPF Terhadap Profitabilitas Bank Syariah. Diponegoro Journal of Management, II (2): 1-10.www.bi.go.idwww.ey.com